Photosensitive and Conductive Hydrogel Induced Innerved Bone Regeneration for Infected Bone Defect Repair (Adv. Healthcare Mater. 3/2023). Issue 3 (24th January 2023) - Jing, Xirui; Xu, Chao; Su, Weijie; Ding, Qiuyue; Ye, Bing; Su, Yanlin; Yu, Keda; Zeng, Lian; Yang, Xu; Qu, Yanzhen; Chen, Kaifang; Sun, Tingfang; et al.
Abstract : Innervation Innervation is the initiating factor for bone regeneration and plays a key regulatory role in subsequent vascularization, ossification, and mineralization processes. A biomaterial that can induce skeletal‐associated neural network reconstruction and bone regeneration with high antibacterial activity is proposed for the treatment of infected bone defects. In article 2201349, Tingfang Sun, Zhiqiang Luo, Xiaodong Guo, and co‐workers load magnesium‐modified black phosphorus nanosheets (BP@Mg) in GelMA for the treatment of infected bone defects. The photosensitive hydrogel has a strong antibacterial activity and improves the local microenvironment. BP@Mg promotes the secretion of Schwann cells and the outgrowth of CGRP+ sensory nerve fibers, thus enhancing the nerve–bone crosstalk and finally realizing innerved bone regeneration.